The Staged Characteristics of the Concept of a Community with a Shared Future for Mankind from the Perspective of Marxist Social Formation - Liu, Ningning (Journal of Social Science and Humanities, 2025)
The community of shared future for mankind” as a concept of global governance has received widespread attention and in-depth discussion in the international community in recent years. This concept emphasizes that in the face of global challenges and the increasing interdependence, countries around the world should work together to jointly address issues such as climate change, resource scarcity, wealth disparity, terrorism, and more, to build a more equitable, just, and sustainable world. Its core concept is not only related to global development and peace but also involves fundamental changes in the structure of global governance and the international order. This article attempts to analyze the phased characteristics of the concept of “community of shared future for mankind” from the perspective of Marxist social formation, exploring how this concept has gradually formed in the context of globalization and demonstrates its inherent historical inevitability and development momentum in practice. The concept of building a community with a shared future for mankind scientifically addresses the era’s question of “where the world is heading and what humanity should do.” It embodies the common values of all humanity, reflects the high degree of unity between China’s development and global development, and holds significant and far-reaching implications for China’s peaceful development and global prosperity. Marxist theory provides profound tools for understanding social change, historical processes, and shifts in global governance, particularly through its historical materialist methodology when analyzing globalization, international cooperation, and cultural transformation. From the perspective of Marxist social formation, this article not only offers a theoretical interpretation of the “community with a shared future for mankind” concept but also seeks to reveal its practical significance amid globalization and global crises. Through this research, we aim to provide a new theoretical lens for understanding the complex interactions within the contemporary international political-economic landscape and the future of global governance.